Psoriasis Dengan Pengobatan Metotreksat - Wizar Putri Melaratna; Adinda Fahira Dyen Matondang (Lembaga Pengembangan Kinerja Dosen, 2023)
Psoriasis is a chronic immune disease of the skin characterized by the accelerated exchange of epidermal cells and a faster-than-normal keratinization process. Psoriation has a variety of clinical manifestations, one of which is gutata psoriasis which has a distinctive image in the form of red spots rising like water droplets with a small diameter that usually does not exceed 1 cm, arises suddenly and disseminates. The case report is about psoriasis being administered with methotrexate. The patient comes with a major complaint in the form of a full-body itch that the patient has been feeling for more than 20 years. On dermatological status in the anterior et posterior thoracalis region, the brachii et antebrachii dextra et sinistra, the femoral region et crusis dextra et sinitra found hypopigmentation plaques with firm, multiple, milier-numular sizes. Patients are treated with methotrexate taken 3 tablets 1x a week, and folic acid 1x1 tablets.